A wave absorbing patch for 700MHz 5G base station in P band and preparation method thereof
By using a wave absorber made of ternary magnetic composite absorber and rubber, the filling quantity and mass ratio is adjusted, the problems of insufficient absorption loss and poor peak frequency band regulation of the wave absorber for 700MHz 5G base stations are solved, and the problem of insufficient absorption loss and poor reflection loss peak frequency band regulation is achieved. It has high electromagnetic wave absorption and signal-to-noise ratio improvement, and has the characteristics of thin wave absorption coating, light surface density and strong absorption performance.
Patent Information
- Application Number
- CN202210502587.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-09
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-05-09
AI Technical Summary
The existing 700MHz 5G base stations have insufficient absorption loss near the 700MHz main frequency, and the peak frequency band regulation effect of reflection loss is poor, resulting in relatively low signal-to-noise and ineffectively reducing clutter interference.
Using a 700MHz 5G base station in P band made of ternary magnetic composite absorber and rubber, the wave absorber patch for 700MHz in P band is used to adjust the filling quantity and mass ratio of ternary magnetic composite absorber to improve impedance matching, and achieve high electromagnetic wave absorption and absorption peaks. Frequency band adjustment, simple preparation process.
It realizes high electromagnetic wave absorption in the 700MHz frequency band, with a reflection attenuation of more than 10dB, and has the advantages of thin absorption coating, light surface density, wide absorption frequency bandwidth, strong absorption performance and good mechanical properties, simplifying the preparation process.
Smart Images

Figure CN114899618B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of absorbing materials, and in particular to an absorbing patch for a 700MHz 5G base station in the P band and a preparation method thereof. Background Art
[0002] With the promotion of 5G technology, a large number of 5G base stations have been built. It is particularly important to conduct electromagnetic compatibility research on 700MHz and 2.1GHz to provide signal-to-noise ratio near this frequency band. Absorbing materials have the advantages of absorption peak frequency band and adjustable loss. As a passive material, they are very suitable for selective absorption of electromagnetic waves in a closed space where the structure is not modified for a long time.
[0003] For the current 700MHz 5G base station absorbing patches, it is expected to have strong absorption loss near the 700MHz main frequency, and have a regulating effect on the 700MHz±1MHz reflection loss peak frequency band, so as to achieve frequency-band adjustable absorption loss, thereby reducing clutter interference and improving the signal-to-noise ratio of related 5G signal frequency bands. Summary of the invention
[0004] The present invention provides an absorbing patch for a 700MHz 5G base station in the P band, which has the advantages of thin absorbing coating, light surface density, wide absorption frequency band, strong absorption performance, good mechanical properties, and simple preparation.
[0005] The present invention also provides a method for preparing an absorbing patch for a 700MHz 5G base station in the P band, which is used to prepare the above-mentioned absorbing patch.
[0006] A wave absorbing patch for a 700MHz 5G base station in the P band is made of a ternary magnetic composite absorber and rubber, wherein the mass ratio of the ternary magnetic composite absorber to the rubber is (72-78): (22-28); wherein,
[0007] The ternary magnetic composite absorbent comprises secondary sintered ferrite, flaky carbonyl iron and flaky sendust, wherein the mass ratio of the secondary sintered ferrite, the flaky carbonyl iron and the flaky sendust is (45-55): (25-35): (15-25);
[0008] The secondary sintered ferrite includes ferric oxide, zinc oxide, cobalt oxide and barium carbonate, and the mass ratio of the ferric oxide, the zinc oxide, the cobalt oxide and the barium carbonate is (77-78.5): (3.5-4.3): (6.5-7.0): (11.0-11.5). The secondary sintered ferrite is prepared by high-temperature solid-phase secondary sintering.
[0009] Preferably, the chemical composition of the flaky carbonyl iron is: Fe ≥ 97.5%, N ≤ 0.8%, C ≤ 0.9%, O ≤ 1.0%; morphology: flake diameter 2-6 μm; bulk density: 1.27-1.35 g / cm 3 .
[0010] More preferably, the chemical composition of the sheet-shaped iron silicon aluminum is: Fe ≥ 84.5%, Si ≤ 10.0%, AI ≤ 6.0%; morphology: sheet diameter 52-67 μm (D50); loose density: 0.34-0.52 g / cm 3 .
[0011] More preferably, the rubber includes silicone rubber and / or chloroprene rubber.
[0012] A method for preparing a 700MHz 5G base station absorbing patch in the P band as described above comprises the following steps:
[0013] S1, preparing secondary sintered ferrite by high temperature solid phase secondary sintering of ferric oxide, zinc oxide, cobalt oxide and barium carbonate in a mass ratio of (77-78.5):(3.5-4.3):(6.5-7.0):(11.0-11.5);
[0014] S2, mixing the secondary sintered ferrite, the flake carbonyl iron and the flake sendust in a mass ratio of (45-55):(25-35):(15-25) by ball milling to prepare a ternary magnetic composite absorbent;
[0015] S3, mixing the ternary magnetic composite absorber and rubber in a mass ratio of (72-78):(22-28), subjecting them to internal mixing, open mixing, sheeting, and high-temperature flat plate vulcanization to obtain an absorbing patch.
[0016] More preferably, the high temperature solid phase secondary sintering comprises the following steps:
[0017] S11, mixing ferric oxide: zinc oxide: cobalt oxide: barium carbonate in a mass ratio of (77-78.5): (3.5-4.3): (6.5-7.0): (11.0-11.5); putting the mixture into a ball mill in a mass ratio of material: steel ball of 1:3, adding deionized water so that the deionized water is 2 mm above the surface of the material, and ball milling for 20-23 hours to obtain a primary ball milled material;
[0018] S12, the primary ball mill material is filtered through an extrusion filter device, and then ventilated and left to stand for 6 to 8 days to obtain a primary wet material;
[0019] S13, briquetting the primary wet material and letting it stand for 4 to 5 days under ventilation;
[0020] S14, performing a primary sintering at a sintering temperature of 1250° C., keeping the temperature for 3 hours, and then crushing and screening to obtain a primary sintered ferrite;
[0021] S15, putting the material into a ball mill with a mass ratio of material to steel ball = 1:3, adding deionized water so that the deionized water is 2 mm above the surface of the material, and the ball milling time is 20-23 hours to obtain secondary ball milled material;
[0022] S16, the secondary ball milling material is filtered through an extrusion filter device, and then ventilated and left to stand for 6 to 8 days to obtain a secondary wet material;
[0023] S17, briquetting the secondary wet material and letting it stand for 4 to 5 days under ventilation;
[0024] S18, performing secondary sintering at a sintering temperature of 1320°C, keeping the temperature for 3 hours, and then crushing and sieving with a 200-300 mesh ultrasonic vibration sieve to obtain secondary sintered ferrite.
[0025] More preferably, the internal mixing time is 15 to 20 minutes, the open mixing time is 60 to 80 minutes, the vulcanization time is 12 to 15 minutes, and the vulcanization temperature is 155 to 170°C.
[0026] The present invention provides a 700MHz 5G base station absorbing patch in the P band, which can at least achieve the following beneficial effects: the impedance matching of the ternary magnetic composite absorber can be improved by conveniently changing the mass ratio of the filling amount of the ternary magnetic composite absorber, so as to achieve high electromagnetic wave absorption and absorption peak frequency band adjustment at a frequency of 700MHz in the P band, and the reflection attenuation is greater than 10dB. The absorbing patch has the advantages of thin absorbing coating, light surface density, wide absorption frequency band, strong absorption performance, good mechanical properties and simple preparation.
[0027] The present invention provides a method for preparing an absorbing patch for a 700MHz 5G base station in the P band, which can be used to simply prepare the absorbing patch. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the reflection loss diagram of the absorber with a filling ratio of 74% (55% flaky sendust + 30% flaky carbonyl iron + 15% secondary sintered ferrite, thickness 4.6mm);
[0029] Figure 2 This is the reflection loss diagram of the absorber with a filling ratio of 72% (50% flake sendust + 25% flake carbonyl iron + 25% secondary sintered ferrite, thickness 6.0 mm);
[0030] Figure 3 This is the reflection loss diagram of the absorber with a filling ratio of 74% (45% flaky sendust + 35% flaky carbonyl iron + 20% secondary sintered ferrite, thickness 4.5mm);
[0031] Figure 4 This is the reflection loss diagram of the absorber with a filling ratio of 78% (55% flaky sendust + 30% flaky carbonyl iron + 15% secondary sintered ferrite, thickness 2.5mm);
[0032] Figure 5 This is the reflection loss diagram of the absorber with a filling ratio of 78% (50% flaky sendust + 25% flaky carbonyl iron + 25% secondary sintered ferrite, thickness 3.0 mm);
[0033] Figure 6 This is the reflection loss diagram of the absorber with a filling ratio of 76% (50% flake sendust + 25% flake carbonyl iron + 25% secondary sintered ferrite, thickness 3.6mm);
[0034] Figure 7 This is the electron microscope image of the secondary sintered ferrite;
[0035] Figure 8 This is an electron microscope image of a sheet of aluminum silicon.
[0036] Fig. 9 This is an electron microscope image of sheet-like carbonyl iron. DETAILED DESCRIPTION
[0037] A specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings, but it should be understood that the protection scope of the present invention is not limited by the specific implementation.
[0038] Embodiment 1:
[0039] An embodiment of the present invention provides a P-band 700MHz 5G base station absorbing patch, which is made of a ternary magnetic composite absorber and rubber, and the mass ratio of the ternary magnetic composite absorber to the rubber is 74:26 (that is, the filling mass ratio is 74wt%);
[0040] The ternary magnetic composite absorber includes secondary sintered ferrite (M), flake carbonyl iron (FCI) and flake iron silicon aluminum (FeSiAl), with a mass ratio of 55:30:15.
[0041] The secondary sintered ferrite includes ferric oxide, zinc oxide, cobalt oxide and barium carbonate, with a mass ratio of 77.8:4.1:6.8:11.3. The secondary sintered ferrite is prepared by high-temperature solid-phase secondary sintering.
[0042] Wherein, the rubber is silicone.
[0043] The method for preparing the above-mentioned 700MHz 5G base station absorbing patch in the P band comprises the following steps:
[0044] S1, preparing secondary sintered ferrite by high temperature solid phase secondary sintering of ferric oxide, zinc oxide, cobalt oxide and barium carbonate in a mass ratio of 77.8:4.1:6.8:11.3;
[0045] S2, mixing the secondary sintered ferrite, flake carbonyl iron and flake iron silicon aluminum in a mass ratio of 55:30:15 by ball milling to prepare a ternary magnetic composite absorbent;
[0046] S3, the ternary magnetic composite absorber and rubber are mixed in a mass ratio of 74:26, and subjected to internal mixing, open mixing, sheeting, and high-temperature flat plate vulcanization to obtain an absorbing patch. Among them, the internal mixing, open mixing, sheeting, and high-temperature flat plate vulcanization are the same as the processes in the prior art, the vulcanization temperature is 158°C, the vulcanization time is 13 minutes, and the flat plate test sample specifications are 1000*1000mm and the thickness is 4.6mm. The internal mixing time is 15 minutes, and the open mixing time is 60 minutes.
[0047] Specifically, high temperature solid phase secondary sintering includes the following steps:
[0048] S11, mixing ferric oxide: zinc oxide: cobalt oxide: barium carbonate in a mass ratio of 77.8:4.1:6.8:11.3; putting the mixture into a ball mill in a mass ratio of material: steel ball of 1:3, adding deionized water so that the deionized water is 2 mm above the surface of the material, and ball milling for 20-23 hours to obtain a primary ball milled material, wherein the material refers to a mixture of ferric oxide, zinc oxide, cobalt oxide, and barium carbonate;
[0049] S12, the primary ball milling material is filtered through an extrusion filter device and placed in a ventilated or sunny place for 6 to 8 days to obtain a primary wet material;
[0050] S13, briquetting the primary wet material and letting it stand for 4 to 5 days under ventilation;
[0051] S14, performing a primary sintering at a sintering temperature of 1250° C., keeping the temperature for 3 hours, and then crushing and screening to obtain a primary sintered ferrite;
[0052] S15, putting the material into a ball mill at a ratio of material to steel ball = 1:3, wherein the material refers to the primary sintered ferrite, adding deionized water so that the deionized water is 2 mm above the surface of the material, and the ball milling time is 20-23 hours to obtain a secondary ball milled material;
[0053] S16, the secondary ball milling material is filtered through an extrusion filter device, and then ventilated and left to stand for 6 to 8 days to obtain a secondary wet material;
[0054] S17, briquetting the secondary wet material and letting it stand for 4 to 5 days under ventilation;
[0055] S18, performing secondary sintering at a sintering temperature of 1320°C, keeping the temperature for 3 hours, and then crushing and sieving with a 200-300 mesh ultrasonic vibration sieve to obtain secondary sintered ferrite.
[0056] The loss diagram of the absorbing patch prepared by the above method is as follows: Figure 1 As shown, the reflection loss at 760MHz reaches -11.6dB.
[0057] Embodiment 2:
[0058] The absorbing patch in this embodiment has a filling rate of 72wt%, and the mass ratio of the secondary sintered ferrite (M), flaky carbonyl iron (FCI) and flaky iron silicon aluminum (FeSiAl) in the ternary magnetic composite absorber is 50:25:25, and the other formulas and proportions are the same as those in Example 1.
[0059] In the preparation method of the absorbing patch in this embodiment, the thickness of the flat test sample is 6 mm, and the rest is the same as that in the first embodiment.
[0060] like Figure 2 As shown, the absorbing patch prepared in this embodiment has a reflection loss of -12.49 dB at 685 MHz, which can achieve selective absorption of noise near the 700 MHz frequency band.
[0061] Embodiment 3:
[0062] The absorbing patch in this embodiment has a filling rate of 74wt%, and the mass ratio of the secondary sintered ferrite (M), flaky carbonyl iron (FCI) and flaky iron silicon aluminum (FeSiAl) in the ternary magnetic composite absorber is 45:35:20. Other formulas and proportions are the same as those in Example 1.
[0063] In the preparation method of the absorbing patch in this embodiment, the thickness of the flat test sample is 4.5 mm, and the rest is the same as that in the first embodiment.
[0064] like Figure 3 As shown, the absorbing patch prepared in this embodiment has a reflection loss of -11.11 dB at 720 MHz, and can selectively absorb noise near the 700 MHz frequency band.
[0065] Comparative Example 1:
[0066] The filling rate of the absorbing patch in this embodiment is 78 wt %, and other formulas and proportions are the same as those in the first embodiment.
[0067] In the preparation method of the absorbing patch in this embodiment, the thickness of the flat test sample is 2.5 mm, and the rest is the same as that in the first embodiment.
[0068] like Figure 4As shown, the reflection loss of the absorbing patch prepared in Comparative Example 1 at 760 MHz is only -6.81 dB, and the loss selective absorption peak is relatively low.
[0069] Comparative Example 2:
[0070] The filling rate of the absorbing patch in this embodiment is 78wt%, and other formulas and proportions are the same as those in Embodiment 2.
[0071] In the preparation method of the absorbing patch in this embodiment, the thickness of the flat test sample is 3 mm, and the rest is the same as that in Embodiment 2.
[0072] like Figure 5 As shown, the reflection loss of the absorbing patch prepared in Comparative Example 2 at 720 MHz is only -7.43 dB, and the loss selective absorption peak is relatively low.
[0073] Comparative Example 3:
[0074] The filling rate of the absorbing patch in this embodiment is 76wt%, and other formulas and proportions are the same as those in Embodiment 2.
[0075] In the preparation method of the absorbing patch in this embodiment, the thickness of the flat test sample is 3.6 mm, and the rest is the same as that in Embodiment 2.
[0076] like Figure 6 As shown, the reflection loss of the absorbing patch prepared in Comparative Example 3 reaches -8.7 dB at 685 MHz, and the loss selective absorption peak is still relatively low.
[0077] The following table shows the data of the above examples and comparative examples:
[0078]
[0079] By changing the composition and the filling rate, the present invention can ensure that the reflection loss RL is ≤-10dB in the frequency band near 700MHz when the film is thick (≥4mm), thereby achieving the selective absorption capability of 700MHz 5G base stations in the P band.
[0080] The above disclosures are only several specific embodiments of the present invention. However, the embodiments of the present invention are not limited thereto. Any changes that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A 700MHz 5G base station absorbing patch in the P band, characterized in that: It is made of a ternary magnetic composite absorbent and rubber, wherein the mass ratio of the ternary magnetic composite absorbent to the rubber is (72-78): (22-28); wherein, The ternary magnetic composite absorbent comprises secondary sintered ferrite, flaky carbonyl iron and flaky sendust, wherein the mass ratio of the secondary sintered ferrite, the flaky carbonyl iron and the flaky sendust is (45-55): (25-35): (15-25); The secondary sintered ferrite includes ferric oxide, zinc oxide, cobalt oxide and barium carbonate, and the mass ratio of the ferric oxide, the zinc oxide, the cobalt oxide and the barium carbonate is (77-78.5): (3.5-4.3): (6.5-7.0): (11.0-11.5). The secondary sintered ferrite is prepared by high-temperature solid-phase secondary sintering.
2. The absorbing patch for a 700MHz 5G base station in the P band as claimed in claim 1, characterized in that: The chemical composition of the flake carbonyl iron is: Fe≥97.5%, N≤0.8%, C≤0.9%, O≤1.0%; morphology: flake diameter 2-6 μm; bulk density: 1.27-1.35 g / cm 3 .
3. The absorbing patch for a 700MHz 5G base station in the P band as claimed in claim 1, characterized in that: The chemical composition of the sheet-shaped iron silicon aluminum is: Fe ≥ 84.5%, Si ≤ 10.0%, AI ≤ 6.0%; morphology: sheet diameter 52-67 μm; bulk density: 0.34-0.52 g / cm 3 .
4. The absorbing patch for a 700MHz 5G base station in the P band as claimed in claim 1, characterized in that: The rubber includes silicone rubber or chloroprene rubber.
5. A method for preparing a 700MHz 5G base station absorbing patch in the P band as claimed in any one of claims 1 to 4, characterized in that: The steps include: S1, preparing secondary sintered ferrite by high temperature solid phase secondary sintering of ferric oxide, zinc oxide, cobalt oxide and barium carbonate in a mass ratio of (77-78.5):(3.5-4.3):(6.5-7.0):(11.0-11.5); S2, mixing the secondary sintered ferrite, the flake carbonyl iron and the flake sendust in a mass ratio of (45-55):(25-35):(15-25) by ball milling to prepare a ternary magnetic composite absorbent; S3, mixing the ternary magnetic composite absorber and rubber in a mass ratio of (72-78):(22-28), subjecting them to internal mixing, open mixing, sheeting, and high-temperature flat plate vulcanization to obtain an absorbing patch.
6. The method for preparing a 700MHz 5G base station absorbing patch in the P band as claimed in claim 5, characterized in that: The high temperature solid phase secondary sintering comprises the following steps: S11, mixing ferric oxide: zinc oxide: cobalt oxide: barium carbonate in a mass ratio of (77-78.5): (3.5-4.3): (6.5-7.0): (11.0-11.5); putting the mixture into a ball mill in a mass ratio of material: steel ball of 1:3, adding deionized water so that the deionized water is 2 mm above the surface of the material, and ball milling for 20-23 hours to obtain a primary ball milled material; S12, the primary ball mill material is filtered through an extrusion filter device, and then ventilated and left to stand for 6 to 8 days to obtain a primary wet material; S13, briquetting the primary wet material and letting it stand for 4 to 5 days under ventilation; S14, performing a primary sintering at a sintering temperature of 1250° C., keeping the temperature for 3 hours, and then crushing and screening to obtain a primary sintered ferrite; S15, putting the material into a ball mill with a mass ratio of material to steel ball = 1:3, adding deionized water so that the deionized water is 2 mm above the surface of the material, and the ball milling time is 20-23 hours to obtain secondary ball milled material; S16, the secondary ball milling material is filtered through an extrusion filter device and allowed to stand for 6 to 8 days under ventilation to obtain a secondary wet material; S17, briquetting the secondary wet material and letting it stand for 4 to 5 days under ventilation; S18, performing secondary sintering at a sintering temperature of 1320°C, keeping the temperature for 3 hours, and then crushing and sieving with a 200-300 mesh ultrasonic vibration sieve to obtain secondary sintered ferrite.
7. The method for preparing a 700MHz 5G base station absorbing patch in the P band as claimed in claim 5, characterized in that: The internal mixing time is 15 to 20 minutes, the open mixing time is 60 to 80 minutes; the vulcanization time is 12 to 15 minutes, and the vulcanization temperature is 155 to 170°C.
Citation Information
Patent Citations
ZnCo doped hexagonal crystal system W-type barium ferrite gyromagnetic material and preparation method thereof
CN106495678A
Absorbing materials and absorbing baseplates and absorbing fins and preparation methods and electronic device
CN106803451A
W-type barium ferrite / carbonyl iron composite waved absorbing silicon sheet and production method thereof
CN107365135A
Microwave ferrite composite material and preparation technology thereof
CN107564656A
FeSiAl / ferrite composite wave-absorbing agent and preparation method thereof
CN107598160A
Cited By
An absorbent for shielding materials of 5G base stations and its preparation method
CN119910186B
